Professional Development of Junior High School Teachers for Sustainable Learning Quality: Pengembangan Profesional Guru SMP untuk Kualitas Pembelajaran Berkelanjutan - Hadi Akmal Lubis Lubis; Tobroni; Joko Widodo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid development of information technology and educational reforms in Indonesia, including the Merdeka Belajar policy, necessitates continuous improvement in teacher quality. Specific Background: Junior high school (JHS) teachers play a critical role in delivering effective education, yet many still face challenges in maintaining professional competence. Knowledge Gap: Existing professional development programs are often fragmented, formalistic, and disconnected from teachers’ actual needs, particularly in the context of aligning national education reforms with global objectives like the SDGs. Aims: This study aims to investigate sustainable professional development (CPD) strategies for JHS teachers that enhance teaching quality within the Merdeka Belajar framework and SDG 4 (Quality Education). Results: Using a qualitative case study at SMP Muhammadiyah Asahan, key strategies identified include needs-based planning, transformative leadership, interactive training, mentoring, and digital learning integration. Novelty: Unlike prior studies, this research offers a comprehensive, context-specific analysis that links national policy with global educational goals, emphasizing collaborative and adaptive approaches to teacher development. Implications: The findings support the development of sustainable, contextualized CPD models that empower teachers as agents of educational transformation and suggest policy refinements to reinforce multi-stakeholder collaboration for long-term impact.Highlight : The main focus of the research is to improve the competence of junior high school teachers through continuous professional development. The integration of Merdeka Belajar and SDGs strengthens the relevance of teacher development programs nationally and globally. The strategy includes needs planning, interactive training, mentoring, and the use of technology and collaboration. Keywords : Sustainable Professional Development, Teacher Competence, Junior High School Teachers, Learning Quality, SDGs (Education)